2022
DOI: 10.1016/j.ecresq.2022.02.002
|View full text |Cite
|
Sign up to set email alerts
|

An ecological perspective on early educator well-being at the start of the COVID-19 pandemic

Abstract: Early educator well-being is increasingly understood as a critical ingredient of high-quality early education and care. The COVID-19 pandemic has threatened educator well-being by exacerbating existing stressors and introducing novel stressors to all aspects of early educators’ lives, and early educators have had differential access to resources to cope with these new circumstances. Using survey data collected between April and June 2020 with a sample of 666 early educators in community-based center, family ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Such conditions could also have harmed children's executive functioning outcomes, which are sensitive to access to high-quality instructional interactions (Fuhs et al, 2018). One signal of the potential for social-behavioral setbacks due to the pandemic is that parents reported worsened home behaviors during remote learning ( Hanno et al, 2022 ).…”
Section: The Learning and Development Of Preschoolers From Low-income...mentioning
confidence: 99%
“…Such conditions could also have harmed children's executive functioning outcomes, which are sensitive to access to high-quality instructional interactions (Fuhs et al, 2018). One signal of the potential for social-behavioral setbacks due to the pandemic is that parents reported worsened home behaviors during remote learning ( Hanno et al, 2022 ).…”
Section: The Learning and Development Of Preschoolers From Low-income...mentioning
confidence: 99%
“…For example, in a systematic review of the effects of COVID-19 pandemic on K-12 education, Huck and Zhang (2021) found that teachers' professional job functions (e.g., lesson planning, assessment) were more challenging in a remote environment, especially having little to no preparation with remote teaching. In another study, Hanno et al (2022) investigated the effects of COVID-19 on educator well-being among a sample of 666 early educators. Not surprisingly, the majority of participants indicated that COVID-19 adversely impacted their mental well-being, approximately half noted its negative impact on their financial well-being, and a quarter of participants reported the influence of the pandemic on their physical well-being.…”
Section: School Functionality and School Personnel's Functioning And ...mentioning
confidence: 99%
“…Coupled with these measures were disruptions of school functionality, namely since the outbreak of the pandemic, students transitioned from fully virtual, to hybrid, and then back to in person learning (Savitz‐Romer et al., 2021). A large body of literature has documented a spectrum of concerns directly linked to COVID‐19 on educators such as mental and financial well‐being, psychological functioning, challenges with practice (e.g., struggling with online teaching), and strategies to support parental involvement (e.g., Hanno et al., 2022; Huck & Zhang, 2021). For example, in a systematic review of the effects of COVID‐19 pandemic on K‐12 education, Huck and Zhang (2021) found that teachers’ professional job functions (e.g., lesson planning, assessment) were more challenging in a remote environment, especially having little to no preparation with remote teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the health and safety of all citizens of the education unit is a top priority that must be considered in setting PTM policies during the Covid-19 pandemic. Therefore, the education unit prepares alternative PTM by continuing to apply the health protocol and PJJ so that parents/guardians of students can choose PTM or PJJ for their children (Hanno, Gardner, Jones, & Lesaux, 2022).…”
Section: Introductionmentioning
confidence: 99%